Akinesia in Parkinsonism. Relation between spontaneous movement (other than tremor) and voluntary movements made on command - Meyer, Carl Ha (1982)
In eleven patients with Parkinsonism there was a strong inverse relationship between the frequency of spontaneous activity of the arms and the degree of fatiguing of repetitive finger movements made upon command. The prevalence of spontaneous arm movement was related inversely (but more weakly) to the time taken to complete a pegboard test or to move clothespegs by hand; it had little association with the speed of linear movement or with simple motor reaction time involving the arm.